An experimental study of support for protest causes and tactics and the influence of conspiratorial beliefs - Morgan, Anthony (Trends & issues in crime and criminal justice, 2024)
We conducted a randomised survey experiment involving 13,301 online Australians. Respondents were asked about their support for environmental, anti-lockdown and sovereign citizen protests. They were randomly allocated to one of three groups presented with different protest tactics—peaceful marching, disrupting traffic and violent clashes with police. Respondents were significantly more likely to oppose violent or disruptive protests than peaceful protests, regardless of the issue or movement in question. The strongest opposition was to anti-lockdown and anti-vaccination protests, followed by protests relating to the sovereign citizen movement. Protests about environmental issues had the most support. The effect of conspiratorial beliefs on support for protests varied by protest cause. Belief in conspiracy theories increased support for protest violence, relative to other tactics. Support for certain protest causes and tactics is shaped by a person’s ideological beliefs.